TREATMENT COMPLIANCE IN PEOPLE WITH TYPE 2 DIABETES AT THUY NGUYEN DISTRICT HEALTH CENTER, HAI PHONG, IN 2022 AND SOME FACTORS RELATED (Vietnam Journal of Community Medicine, 2024)
Objectives: Describe the status of treatment adherence and some related factors in patients with type2 diabetes at Thuy Nguyen District Health Center, Hai Phong, in 2022Research method: An analytical cross-sectional study was performed on 245 patients.Results: The majority of patients were prescribed oral drugs at 78.8%, and the rate of using 2 drugsin combination was the highest at 46.9%. The overall adherence rate was 15.9%.Some factors related with statistical significance to general adherence to treatment for type 2 diabetes:the rate of adherence to drug use in the treatment of women is 2.22 times higher than that of men(p
Keywords: Diabetes type 2, adherence to treatment, Thuy Nguyen District Medical Cente